Beyond the Inhibition of Return of Attention: Reduced Habituation to Threatening Faces in Schizophrenia - Hu, Frank; He, Shuchang; Fan, Zhiwei; Lupiáñez, Juan (Frontiers in Psychiatry, 2014)
Attention deficits are prominent among the core symptoms of schizophrenia. A recent meta- analysis has suggested that patients with schizophrenia have a deficit in endogenous disengagement of attention. In this research, we used a standard spatial cueing paradigm to examine whether the attention deficit of such patients is due to impaired attentional disengagement or defective novelty detection/habituation processes. In a spatial cueing procedure with peripheral non-predictive cues and a detection task, we manipulated the valence of either the cue or the target (i.e., a threatening vs. scrambled face) in two separate experiments. The control group exhibited a smaller inhibition of return (IOR) effect only when the target had an emotional load, not when the cue had an emotional load. In the patient group, a larger emotional effect appeared when the threatening face was the target; by contrast, no effect of valence was observed when the threatening face was the cue: IOR was delayed or completely absent independently of valence. The present findings are in conflict with the hypothesis that IOR is due to the disengagement of attention and the subsequent inhibition to return. Instead, they seem to suggest a cost in detecting new information at a previously cued location. From this perspective, it seems that patients with schizophrenia might have a deficit in detecting new information and considering it as new in the current context.